Assessment of Immune Response Following Dendritic Cell-Based Immunotherapy in Pediatric Patients With Relapsing Sarcoma - Fedorova, Lenka; Mudry, Peter; Pilatova, Katerina; Selingerova, Iveta; Merhautova, Jana; Rehak, Zdenek; Valik, Dalibor; Hlavackova, Eva; Cerna, Dasa; Faberova, Lucie; Mazanek, Pavel; Pavelka, Zdenek; et al. (Frontiers in Oncology, 2019)
Monocyte-derived dendritic cell-based vaccines loaded with tumor-self antigens represent a novel approach in anti-cancer therapy. We evaluated DC-based anti-cancer immunotherapy in an academic Phase I/II clinical trial for children, adolescent and young adults with progressive, recurrent or primarily metastatic high-risk tumors. The primary endpoint was safety of intradermal administration of manufactured dendritic cells. Here we focused on relapsing high-risk sarcoma subgroup representing a major diagnosis in DC clinical trial. As a part of peripheral blood immunomonitoring, we evaluated quantitative association between basic cell-based immune parameters. Furthermore, we describe the pattern of these parameters and their time-dependent variations during the DC vaccination in the peripheral blood immunograms. The peripheral blood immunograms revealed distinct patterns in particular patients in the study group. As a functional testing we evaluated immune response of patient T-cells to the tumor antigens presented by DCs in the autoMLR proliferation assay. This analysis was performed with T-cells obtained prior to DC ITx initiation and with T-cells collected after 5th dose of DCs demonstrating that the anti-cancer DC-based vaccine stimulates a pre-existing immune response against self-tumor antigens. Finally, we present clinical and immunological findings in a Ewing's sarcoma patient with interesting clinical course. Prior to DC therapy, we observed prevailing CD8+ T-cell stimulation and low immunosuppressive M-MDSC and Tregs. This patient was subsequently treated with 19 doses of DCs and experienced substantial regression of metastatic lesions after 2nd disease relapse and was further rechallenged with dendritic cells. In this patient, functional ex vivo testing of autologous T-cell activation by manufactured DC medicinal product during the course of DC immunotherapy revealed that personalized anti-cancer DC-based vaccine stimulates a pre-existing immune response against self-tumor antigens and that the T-cell reactivity persisted for the period without DC treatment and was further boosted by DC rechallenge. TRIAL REGISTRATION NUMBER: EudraCT 2014-003388-39